An appraisal of folates as key factors in cognition and ageing-related diseases. Issue 5 (8th March 2020) - Craenen, Kai; Verslegers, Mieke; Baatout, Sarah; Abderrafi Benotmane, Mohammed
Abstract: Folic acid (FA) is often consumed as a food supplement and can be found in fortified staple foods in various western countries. Even though FA supplementation during pregnancy is known to prevent severe congenital anomalies in the developing child (e.g., neural tube defects), much less is known about its influence on cognition and neurological functioning. In this review, we address the advances in this field and situate how folate intake during pregnancy, postnatal life, adulthood and in the elderly affects cognition. In addition, an association between folate status and ageing, dementia and other neurodegenerative disorders such as Alzheimer's disease, Parkinson's disease and amyotrophic lateral sclerosis is discussed. While its role in the incidence and severity of these diseases is becoming apparent, the underlying action of folates and related metabolites remains elusive. Finally, the potential of FA as a nutraceutical has been proposed, although the efficacy will highly depend on the interplay with other micronutrients, the disease stage and the duration of supplementation. Hence, the lack of consistent data urges for more animal studies and (pre)clinical trials in humans to ascertain a potential beneficial role for folates in the treatment or amelioration of cognitive decline and ageing-related disorders.